2014
DOI: 10.1016/s1872-2067(14)60155-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of ceria for the selective catalytic reduction of NOx with NH3

Abstract: The selective catalytic reduction of NOx with NH3 (NH3-SCR) is one of the widely used NOx control strategies for stationary sources (particularly for power plants) and mobile sources (particularly for diesel vehicles). The application is aimed at meeting the increasingly stringent standards for NOx emissions. Recently, ceria has attracted much attention for its applications in NH3-SCR catalysts owing to its unique redox, oxygen storage, and acid-base properties. In this article, we comprehensively review recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(50 citation statements)
references
References 56 publications
0
48
0
1
Order By: Relevance
“…Ce has been widely used as the promoter to improve the thermal stability and catalytic activity for the transition metal oxide catalyst. 35,36 Based on the proposed three-step catalytic mechanism, the reaction processes of NO oxidation catalyzed by ZSM5-Co and ZSM5-Mn based on Al/Ce as the active T-center are calculated and obtained by the UB3LYP/SDD method. The reaction process of NO oxidation catalyzed by ZSM5-Co-Ce is shown in Fig.…”
Section: No Oxidation Catalyzed By Zsm5-co/mnmentioning
confidence: 99%
“…Ce has been widely used as the promoter to improve the thermal stability and catalytic activity for the transition metal oxide catalyst. 35,36 Based on the proposed three-step catalytic mechanism, the reaction processes of NO oxidation catalyzed by ZSM5-Co and ZSM5-Mn based on Al/Ce as the active T-center are calculated and obtained by the UB3LYP/SDD method. The reaction process of NO oxidation catalyzed by ZSM5-Co-Ce is shown in Fig.…”
Section: No Oxidation Catalyzed By Zsm5-co/mnmentioning
confidence: 99%
“…In the pattern of 30Ce-V 2 O 5 /TiO 2 , the doped Ce exists mainly in the form of CeO 2 and part of CeVO 4 . It was found that CeO 2 can effectively improve the catalytic activity and make the reaction temperature window wider [18]. However, the formation of CeVO 4 has a certain suppression to the improvement of catalytic activity [23].…”
Section: Xrdmentioning
confidence: 99%
“…MnO has attracted significant attention because of its various types of labile oxygen species [16,17]. Recently, Ce-doped catalyst has been found to reduce the reaction temperature significantly and has high catalytic activity and selectivity [18]. Mn-doped catalyst has shown excellent lowtemperature activity, lower apparent active energy, and better ion dispersion than those of most previously reported SCR catalysts [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen oxides (NO x ), derived from stationary sources (such as fossil energy plants) and mobile sources (such as diesel engines), could cause acid rain, greenhouse effects, photochemical smog, haze, and other environmental issues, all of which are harmful to the ecological environment and human health . Recently, with increasingly stringent emission standards, several techniques are employed to remove NO x .…”
Section: Introductionmentioning
confidence: 99%